Home space solution / Kamil Khalili Abdullah … [et al.] - Abdullah, Kamil Khalili; Norzaidi, Nabil Harith Riffat; Elli, Muhammad Adil; Zailani, Muhammad Fitri; Radiman, Samsiah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Our innovation consists of space and interior innovation. Space innovation: The built-up area of the house will increase from 365.85ft to 439.96ft. Furniture innovation, the usage area will increase from 365.85ft to 1188.28ft. How it can be done? Let's find out! Innovating space and furniture by adding precast rooms, multipurpose area and multi-functional furniture. The advantages are reduced cost as there are no rebuilding required, increase space with the additional rooms fitted to the original house. lt is also fulfilling the new buildings requirement which requires at least 3 rooms for every new house build and shorter construction timeless than half of conventional cast in-situ construction. The impacts are low income earner can afford it, completing the innovation within short time limit, reducing cost by using -space and interior innovations and converting the existing house into a more comfortable 3-room house. Commercial potential is it can be implementing our interior and space innovations for hotels, apartments, hospitals, schools and other existing public houses.